Reduced height of short day induced bud scale complex may partly explain early bud burst in Norway spruce seedlings - Luoranen, Jaana; Sutinen, Sirkka (The Finnish Society of Forest Science, 2017)
Short day (SD) treatment is used as a dormancy induction in forest tree seedling nurseries in the boreal forest zone. However, SD treatment has caused early bud burst in the following spring, which may expose the seedlings to spring frosts. Because the mechanisms affecting earlier bud burst in SD treated seedlings are not fully understood yet, here we have studied the effect of SD treatment on the structure of buds in Norway spruce [Picea abies (L.) Karst.] seedlings. Seedlings were exposed to SD treatments or natural (CTRL) light and photoperiod in July in a nursery in Central Finland. The experiments included two lots of seedlings over two summers and the analyses were done under a stereo microscope. SD treatment advanced initiation of bud scales and formation of needle primordia, and thus the formation period was shorter in CTRL seedlings. In mature buds, no differences in primordial shoots were found between the treatments, whereas notable differences were found in bud scales. The SD buds had fewer and shorter bud scales than the CTRL buds. This led to significantly shorter bud scale complex and, consequently, to shorter buds in SD than in CTRL seedlings. Buds and needles matured earlier in SD treated seedlings. In the following spring, the primordial shoots started to elongate in both treatments around mid-May, when the SD buds started to break down, whereas CTRL buds started to break down in late May. The fewer number and shorter height of protective bud scales may expose buds to harsh winter temperatures and early loss of scales may predispose the SD buds to spring frosts.
Keywords: bud scale complex; elongation; primordia; shape; Picea abies